Hydrothermal syntheses, crystal structures, and optical properties of transition metal selenidostannates. Issue 22 (17th December 2019) - Li, Shufen; Wei, Zheng; Chen, Niannian; Gao, Yan; Jia, Dingxian
Abstract: New organic–inorganic hybrid selenidostannates [Mn(2, 2′-bipy)2 2 ( µ 2 -Sn2 Se6 )] (1 ) and [TM(2, 2′-bipy)3 ]2 [Sn3 Se7 ]2 ·(2, 2′-bipy)·H2 O (TM = Co (2 ), Ni (3 ); 2, 2′-bipy = 2, 2′-bipyridine) were prepared under hydrothermal conditions. In 1, two edge-sharing [SnSe4 ] tetrahedra condense to form a dimeric [Sn2 Se6 ] 4– unit. The [Sn2 Se6 ] 4– unit is a tetradentate chelating ligand via four terminal Se atoms to join two unsaturated [Mn(2, 2′-bipy)2 ] 2+ complexes, forming a neutral complex [Mn(2, 2′-bipy)2 2 ( µ 2 -Sn2 Se6 )]. Compounds 2 and 3 consist of extended [Sn3 Se7 ] 2– selenidostannate anions, octahedral [TM(2, 2′-bipy)3 ] 2+ complex cations, and 2, 2′-bipy and H2 O molecules. The structural features of 2 and 3 are coexistence of both 1-D [ S n 3 S e 7 2 − ] ∞ 1 and 2-D [ S n 3 S e 7 2 − ] ∞ 2 polymeric anions. The 1-D [ S n 3 S e 7 2 − ] ∞ 1 chain is constructed by interconnection of the secondary building units (SBUs) Sn3 Se9 via sharing two Se atoms, while the 2-D [ S n 3 S e 7 2 − ] ∞ 2 layer is constructed by Sn3 Se10 SBUs via sharing three Se atoms. Compounds 1 –3 exhibit narrow semiconducting band gaps varying in the range of 1.95–2.14 eV. Compound 2 displays higher photocatalytic activity than 1 on the degradation of crystal violet in water under visible irradiation. Graphical Abstract: